2011
DOI: 10.6008/ess2179-6858.2011.001.0002
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A Mata Atlântica destaca-se como o principal bioma brasileiro no que se refere a estudos e programas de conservação da biodiversidade, embora ainda seja alvo de inúmeras ações antrópicas que compromete a eficácia dessas medidas de proteção ambiental. Os hilídeos possuem doze modos reprodutivos, sendo onze registrados na Mata Atlântica. As variações ocorrentes nas estratégias reprodutivas dos anuros são combinações de atributos morfológicos, fisiológicos e comportamentais, adaptados a condições ambientais. O ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, Scinax alter, which was the most abundant species in this study, is a species commonly occurring in open areas and is often found in vegetation above ponds and other standing water areas (Carvalhoe-Silva & Kwet 2010). Another species was also recorded exclusively in flooded environments was Boana semilineata, which is usually associated with water bodies (Mendes et al 2012) and is often found on herbaceous plants at the margins of swamps and creeks (Lisboa et al 2011). In contrast, only Haddadus binotatus was recorded exclusively in the forest environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Scinax alter, which was the most abundant species in this study, is a species commonly occurring in open areas and is often found in vegetation above ponds and other standing water areas (Carvalhoe-Silva & Kwet 2010). Another species was also recorded exclusively in flooded environments was Boana semilineata, which is usually associated with water bodies (Mendes et al 2012) and is often found on herbaceous plants at the margins of swamps and creeks (Lisboa et al 2011). In contrast, only Haddadus binotatus was recorded exclusively in the forest environment.…”
Section: Discussionmentioning
confidence: 99%
“…The predation was observed in Reserva Biológica de Saltinho (08°43ʹ43ʺS, 35°10ʹ39.8ʺW), Tamandaré, southern coast of Pernambuco state, Brazil. The reserve has a total area of 562.25 ha composed of the Ombrophilous Dense Forest (Lisboa et al, 2011;ICMBio, 2015). In previous studies of other Atlantic Forest fragments, T. pusillus has been observed only as the predator of spiders, crickets, cockroaches, and moths (Lira pers.…”
mentioning
confidence: 99%